Evaluation of phosphatic fertilizers of different solubility for common bean using isotopic methods. - García-Altunaga, Aurelio; Hernández-Barrueta, Germán; Nuviola-Montoya, Antonio; Herrero-Echeverría, Grisel; Méndez-Pérez, Nancy; Jecques-Drevon, Jean (Agronomía Mesoamericana, 2005)
Glasshouse experiments were carried out in the Experimental Station La Renée located in Habana province in the year 2003. The objective of this study was to evaluate the effectiveness of phosphorus (P) sources varying in solubility for common bean (Phaseolus vulgaris L.) nutrition using the isotopic dilution method, growing under two soils, Acrisol and Rhodic Ferralsol. The P sources evaluated in both soils were phosphate rock (PR) Trinidad de Guedes and PR partially solubilized at 50% with H2SO4, namely FPA 50, whereas single super phosphate (SS) and triple super phosphate (TSP) were used in the Acrisol and Rhodic Ferralsol soils, respectively. The common bean genotypes were BAT 477, DOR 364, DOR 390 and Censa, and BAT 58, BAT 477, DOR 364 and CC-25-9(N) in the Acrisol and Rhodic Ferralsol soils, respectively. Dry matter production, P extraction, and the fraction and quantity of P in plants obtained from different P sources were evaluated, and P use efficiency of each P fertilizer were calculated. Single and triple super phosphate and FPA 50 were effective P fertilizers in both soils whereas RF was not.